Penguatan Kompetensi Guru PAUD Dalam Mengembangkan Media Edutainment Islami Digital Sebagai Produk Edupreneur - Rahayu, Evi; Seprya, Roby; Guswanti, Nelia; Maghfiroh, Shofia; Fernianti, Asri; Nafisa Putri, Ainama; Rama Sayfruni, Nofiani (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
This community service activity aims to improve the competence of Early Childhood Education (PAUD) teachers in developing digital-based Islamic edutainment learning media while fostering a spirit of edupreuneurship. The methods used included needs analysis, training, workshops, intensive mentoring, and participatory evaluation. The results of the activity showed that PAUD teachers were able to create digital Islamic learning media in the form of simple animated videos, digital interactive books, and Islamic audio-visual content that was engaging for children. Furthermore, the teachers understood strategies for packaging these products to have economic value as edupreuneurial products. This activity successfully increased digital literacy, creativity, and entrepreneurial awareness among PAUD teachers, thus supporting a more innovative and effective learning transformation